(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

If (the integral from -3 to 2)f(x)dx=-1, (the integral from -1 to 5)f(x)dx=8, and (the integral from -3 to 5) f(x)dx=6, then (the integral from -1 to 2)f(x)dx= ?

2. Relevant equations

This is the part I'm struggling with.

3. The attempt at a solution

I know that the answer is as follows:

Note that (the integral from -3 to -1) f(x)dx= (the integral from -3 to 5)f(x)dx- (the integral from -1 to 5) f(x)dx= 6-8= -2. So (the integral from -1 to 2) f(x)dx= (the integral from -3 to 2) f(x)dx- (the integral from -3 to -1) f(x)dx= -1-(-2)= 1

I just don't understand what rule allows you to do the above.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Integrating with unknown method

**Physics Forums | Science Articles, Homework Help, Discussion**